Serotypes and Shiga toxin genotypes among Escherichia coli isolated from animals and food in Argentina and Brazil - Guth, Beatriz E C (2003)
Fil: Guth, Beatriz E C. Departamento de Microbiologia, Imunologia e Parasitologia, Universidade Federal de São Paulo; Brasil.